PENDIDIKAN KESEHATAN PENERAPAN PEDOMAN “PEMAHAT ASIK” (PERILAKU MAKAN SEHAT DAN AKTIVITAS FISIK) UNTUK MENCEGAH MASALAH STATUS GIZI PADA ANAK USIA SEKOLAH - Puspita, L.M.; Kurniasari, N.M.D.; Dewi, A.A.N.T.N.; Sukmadewi, P.M. (Buletin Udayana Mengabdi; Vol 23 No 6 (2024): Buletin Udayana Mengabdi, 2024)
Eating behavior and physical activity are factors that influence nutritional status in children. Increasing children's knowledge about healthy eating behavior and carrying out sufficient activities needs to be done to support the implementation of good behavior. Providing health education can increase understanding of healthy eating behavior and optimize the implementation of physical activity. Therefore, health education is needed for children and parents so that they can understand healthy eating behavior and adequate physical activity so that they can optimize children's nutritional status. The aim of this activity is to provide knowledge and information to students about healthy eating behavior and examples of physical activities that elementary school students can do. The method of this activity is in the form of lectures, question and answer discussions,and giving pretest and posttest questionnaires. The activity was attended by students in grades 4-6 and accompanied by the teacher in charge. The results of the questionnaire analysis showed that there was an increase in students' knowledge after being given health education. The conclusion and implication is that students can implement healthy eating behavior and do sufficient physical exercise so can optimizing the nutritional status of school-aged children. Keywords: eating behavior, nutritional status, physical activity, school age.